Effects of an Educational Film About Body Donors on Students' Empathy and Anxiety Levels in Gross Anatomy. Issue 4 (25th April 2019) - Iaconisi, Julia; Hasselblatt, Friederike; Mayer, Benjamin; Schoen, Michael; Böckers, Tobias Maria; Böckers, Anja
Abstract : While most German anatomy institutes provide only limited information about body donors and their lives, students have expressed a desire to learn more about these individuals, especially about their motivations to donate their bodies for the sake of medical education. In order to gratify this wish, as well as to further humanize body donors, an educational film was compiled, and a study designed to capture the film's effects on medical students. This is the first study using standardized, validated psychological tools to evaluate the impact of an educational film about body donors on students' empathy and psychological stress levels. The study followed a longitudinal, controlled, and cluster randomized design, including 77 (48 females/29 males) participants who watched the video either before, midway, or after the dissection course. Questionnaires were completed at four points in time applying the Jefferson Scale for Empathy (JSPE‐S) and the Interpersonal Reactivity Index (IRI) to measure empathy. Psychological stress levels were recorded by the Brief Symptom Inventory (BSI). Overall, students recommended the film to be shown to all students (median 6.0; maximum on the six‐point Likert scale). Viewing the film revealed no significant changes between study groups or over time in JSPE‐S sum scores. All groups demonstrated a significant reduction of BSI values before the dissection course actually started and increased values during the course, but both developments appeared not to be associated with the intervention. Overall, the educational film did not correlate with any negative effects on students' empathy and psychological stress levels, and it was strongly approved of by students, as it provided more humanizing personal information about body donors without violating their anonymity.